NG2/HMPG modulation of human articular chondrocyte adhesion to type VI collagen is lost in osteoarthritis. - Midwood, K; Salter, D (2001)
NG2/human melanoma proteoglycan (HMPG) is a chondroitin sulphate proteoglycan (CSPG), expressed by chondrocytes in fetal and in normal and osteoarthritic (OA) adult articular cartilage. NG2/HMPG is a receptor for extracellular matrix proteins, including type VI collagen, and regulates beta1 integrin binding to fibronectin. This study was undertaken to identify whether NG2/HMPG had similar activities in human articular chondrocytes (HACs). Normal and OA adult HAC adhesion to fibronectin, type II or type VI collagen was assessed using a methylene blue assay. The requirement for integrins, NG2/HMPG, and integrin-associated signalling molecules was investigated using anti-beta1 integrin and anti-HMPG antibodies and pharmacological inhibitors of signalling molecules. The adhesion of normal and OA HACs to fibronectin, type II and type VI collagen was beta1 integrin-dependent. Normal HAC adhesion to type VI collagen was stimulated by anti-HMPG antibodies. This effect was inhibited by pertussis toxin. Anti-HMPG antibodies had no effect on OA chondrocyte adhesion to type VI collagen, or on normal and OA cell adhesion to fibronectin and type II collagen. The results show that NG2/HMPG modulates integrin-mediated interactions of normal HACs with type VI collagen. Loss of this activity may be of importance in the progression of osteoarthritis.